(untitled) (KYAMC Journal, 2025)
Therapeutic Plasma Exchange (TPE) is a vital extracorporeal procedure used in the management of various neurological, autoimmune and hematological disorders by eliminating pathological plasma components such as autoantibodies, immune complexes, toxins and inflammatory mediators. Its therapeutic efficacy has been particularly notable in conditions such as Guillain-Barré Syndrome (GBS), Thrombotic Thrombocytopenic Purpura (TTP) and myasthenia gravis. TPE works through apheresis technology, applying principles of mass transfer and diffusion to restore immune homeostasis and reduce disease burden. This review explores the current clinical applications of TPE, its underlying mechanisms and patient outcomes based on existing literature. Additionally, it highlights the procedural variations including intermittent and continuous TPE, centrifugation and filtration-based methods, and discusses both the clinical benefits and potential complications associated with the therapy. Furthermore, the review examines the critical socioeconomic challenges faced in implementing TPE in low-resource settings, such as limited healthcare infrastructure, economic barriers, policy gaps and lack of awareness. Emerging research also points to potential new indications for TPE, including its adjunctive role in managing severe COVID-19 cases and certain hepatic, dermatological and toxicological emergencies. As the therapeutic landscape evolves, efforts must be made to optimize treatment protocols, ensure standardized practices and make TPE more accessible across healthcare systems worldwide. Addressing these gaps is crucial for translating its proven benefits into broader clinical impact. KYAMC Journal Vol. 15, No. 04, January 2025: 189-194